2018
DOI: 10.1111/exd.13764
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the extranasal OR2A4/7 expressed in human melanocytes

Abstract: Olfactory receptors (ORs) were first described as specialized chemoreceptors in the nasal epithelium. In the last two decades, ORs have also been detected to be functionally expressed and active in different nonolfactory tissues of the human body, because they used to react to specific odour stimuli. In this study, we conducted a characterization of the extranasal OR2A4/7 expressed in primary human melanocytes and sections of the human skin. OR2A4/7 expression could be demonstrated at the transcript and protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 57 publications
(77 reference statements)
0
22
0
Order By: Relevance
“…The current study showed that OR10A6, OR2AG2, and OR11H4 RNA transcripts and proteins are expressed both in vitro in keratinocytes and ex vivo in skin biopsies. These findings are not surprising since other ORs have already been described in skin cells, such as OR2AT4, OR6M1, OR5V1, OR11A1, OR6V1 [ 16 ], OR2A4/7, and OR51B5 in keratinocytes [ 17 ], or OR2A4/7 and OR51E2 in melanocytes [ 18 , 19 ]. Interestingly, we noticed that the expression patterns of the three ORs differ between skin explants and epidermis.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…The current study showed that OR10A6, OR2AG2, and OR11H4 RNA transcripts and proteins are expressed both in vitro in keratinocytes and ex vivo in skin biopsies. These findings are not surprising since other ORs have already been described in skin cells, such as OR2AT4, OR6M1, OR5V1, OR11A1, OR6V1 [ 16 ], OR2A4/7, and OR51B5 in keratinocytes [ 17 ], or OR2A4/7 and OR51E2 in melanocytes [ 18 , 19 ]. Interestingly, we noticed that the expression patterns of the three ORs differ between skin explants and epidermis.…”
Section: Discussionmentioning
confidence: 69%
“…Previous OR studies in keratinocytes have demonstrated that OR agonists can activate the cAMP intracellular pathway [ 18 , 19 ]. Accordingly, within 30 min of application, the rose extract increased cAMP levels in NHEK ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations